Interactive Video-Based Learning with Edpuzzle: A Tool for Understanding Intermolecular Forces - Sailendra, Pingkan Ramadhan; Erlina*, Erlina; Ulfah, Maria; Enawaty, Eny; Nizam, Dinna Nina Mohd (Universitas Syiah Kuala, 2025)
Students often encounter difficulties in understanding abstract chemistry concepts, particularly in the topic of intermolecular forces. These challenges can lead to misconceptions and hinder their understanding of subsequent material. The difficulty in visualizing submicroscopic and symbolic aspects, along with the lack of effective learning media, contributes to these issues. This study aims to assess the validity and responses of students and lecturers towards the interactive animated video on intermolecular forces (VIMFs) assisted by edpuzzle to enhance conceptual understanding. The method used in this is research and development with the ADDIE model. Data collection was conducted through literature review, observation, interviews, and tests (validity instruments and response questionnaires). The developed video was validated by experts in terms of media, content, and language aspects. Response testing was carried out with three lecturers and 9 students in a one-to-one trial, and 21 students in a small group trial. The validity test results showed that the developed instructional video's validity percentage in terms of content and language was 94.9, and 95.2% for media, with an average percentage of 95.05. The average percentage of lecturer responses to the developed video was 93.9, categorized as excellent, while the student responses in the one-to-one trial were 95.9, and 93.4% in the small group trial, both also categorized as excellent. Thus, the interactive animated VIMFs assisted by edpuzzle received excellent responses from both lecturers and students